Penggunaan Kombinasi Pati Bengkuang Avicel Ph101 sebagai Bahan Pengisi Co-Process Tablet Isoniazid Cetak Langsung - Syofyan, Syofyan; Yelni, Ezi Afri; Azhar, Rieke (Jurnal Sains dan Teknologi Farmasi, 2012)
Starch yam bean (Pachyrrhizus erosus Urban) is tablet excipient with poor of both flowability and compressibility which can not be used as diluents of direct tablet compression. The purpose of this research is to know the influence of the combination avicel PH101 â starch as a filler material co-process. Tablet made with direct compression method with isoniazid as a model drug. Results of the study show that the formula 4 (Avicel PH101 concentration with 4%) can produce co-process with mechanical and physical properties of compresibilitas-the most good, as for the evaluation of isoniazid tablets do not meet the requirements of violence and friabilytas on all formula. In summary, use of Co-Process yam bean starch â Avicel PH101 with 0-4% Avicel PH101 concentration was not produced a tablet that meet the requirements.